2007
DOI: 10.1097/01.rli.0000252496.74242.0b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurements of Perfusion and Permeability of Oropharyngeal and Oral Cavity Cancer, Recurrent Disease, and Associated Lymph Nodes Using First-Pass Contrast-Enhanced Computed Tomography Studies

Abstract: Perfusion CT of oropharyngeal and oral cavity cancer in clinical routine is feasible and helps outlining the malignant tissue as well as differentiating recurrent disease from nonspecific post-therapeutic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 18 publications
5
67
2
Order By: Relevance
“…In our work, T stage was marginally significant for predicting local outcome. Reinforcing this evidence, the weak predictive value (P Ͻ .05) of the T stage for local tumor control in the oropharynx for patients treated with curative surgery or radiation therapy 24,25 and the weak or nonsignificant correlation between the T stage and perfusion-associated parameters 4,11,13 make it hard to predict only on the basis of T. This difficulty highlights the role of perfusion measurements in patients with neoadjuvant chemoradiation. [26][27][28] Finally, the perfusion estimations in our study did not have any predictive value for OS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, T stage was marginally significant for predicting local outcome. Reinforcing this evidence, the weak predictive value (P Ͻ .05) of the T stage for local tumor control in the oropharynx for patients treated with curative surgery or radiation therapy 24,25 and the weak or nonsignificant correlation between the T stage and perfusion-associated parameters 4,11,13 make it hard to predict only on the basis of T. This difficulty highlights the role of perfusion measurements in patients with neoadjuvant chemoradiation. [26][27][28] Finally, the perfusion estimations in our study did not have any predictive value for OS.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8] In particular, the necessity to detect early response to therapy and avoid any time delay in nonresponders has led to examining the predictive value of perfusion imaging, which might help in tailoring the therapy regimen on an individual basis. 9,10 Early proponents of perfusion studies have also demonstrated in a clinical setting that semi-or quantitatively estimated tumor perfusion might predict the outcome after definitive radiation therapy.…”
mentioning
confidence: 99%
“…3, by assuming appropriate values for the model parameters F, v 1 , k 21 , and k 12 . The parameter values used in this study were obtained from a previous study 8 in our institution after institutional review board approval and informed consent from the patients as well as from similar studies in literature. [9][10] These parameter values are F = 70 ml/min/100 g, v 1 = 5 ml/100 g, k 21 = 3.4 min −1 , and k 12 =0.85 min −1 , giving PS= 17 ml/min/100 g.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…On the basis of the selected optimal values for N ICS , Δt, and T, we then consider decreasing values of N in the attempt to identify the smallest value of N that do not compromise on the accuracy of the perfusion parameters. In this set of simulation experiments, the perfusion values assumed were again F=70 ml/min/100 g, v 1 =5 ml/100 g, and PS=17 ml/min/100 g. 8 After defining the optimal scan duration and number of scans, the acquisition protocol was applied in a patient with a head and neck tumor (left parotid gland) after informed consent was obtained. A single 12-mm-thick tumor slab was examined using a 16-row multislice CT scanner (Somatom 16, Siemens Medical Systems, Erlangen, Germany).…”
Section: Simulation Experiments #1mentioning
confidence: 99%
See 1 more Smart Citation